P72 Prevalence and outcomes of unexpected findings in the liverpool healthy lung project (LHLP). (12th November 2019) - Cheng, Y; Field, JK; Gaynor, E; Timoney, M; Arvanitis, R; McCann, C; Hill, S; Fidoe, D; Mason, S; Ledson, M
Abstract : Background: It is considered that early intervention of the clinical significant unexpected findings (UFs) would have a major impact on patients' health. However, how to best differentiate the level of significance of these UFs requires further investigation. Methods: The radiological reports for the Liverpool Health Lung Project (LHLP) were captured as part of the NHS clinical reporting system. Radiologists flag an alert to a UF if it is considered to pose a significant adverse health impact (namely alerted UFs [AUFs]). In addition, we also used the term 'potentially significant UFs (PUFs)' which is commonly used in other studies and defined as incidental findings requiring further follow-up or evaluation. The diagnostics, outcomes and related adverse events of the PUFs and AUFs were followed up for the LHLP to 30 May 2019. The attitudes towards the reporting of UFs were also investigated. Results: From Apr 2016 to Mar 2019, 3486 participants have undergone baseline LDCT screening, of which 319 had a repeat CT scan. 130 patients (3.7%) had 132 AUFs, and another 207 patients (6.0%) had 213 extra PUFs (Table below for the outcomes of the AUFs). Seventeen malignancies were diagnosed in total (14 in the AUFs and 3 in the PUFs), including 13 (0.37%) extra-pulmonary and four pulmonary cancers. Only two patients experienced postoperative complications in the PUF group. Two out of the ten deaths died from AUF-related causes. Conclusion: Radiologists have an important role in reporting, interpretation and communication of incidental findings in lung cancer CT screening projects. The clinical findings identified in the AUF group had a significant clinical impact; however, the PUF findings need to be reassessed.